Identification of a New Giant Emrbryo Allele, and Integrated Transcriptomics and Metabolomics Analysis of Giant Embryo Development in Rice - Hu, Zejun; Xiong, Qiangqiang; Wang, Kai; Zhang, Lixia; Yan, Ying; Cao, Liming; Niu, Fuan; Zhu, Jinyan; Hu, Jinlong; Wu, Shujun (Frontiers in Plant Science, 2021)
Rice embryos are rich in high-quality protein, fat, vitamins and minerals, representing the most important nutritional part of brown rice. However, the molecular mechanism of rice embryo development is poorly understood. In this study, two rice cultivars with contrasting embryo size (the giant embryo cultivar Dapeimi and the normal embryo cultivar 187R) were used to explore excellent genes controlling embryo size, and the developed near-isogenic lines (NILs) (NIL-D, which has the giant embryo phenotype, and its matching line, NIL-X) were used to explore transcript and metabolic properties in the earlier maturation stage of giant embryo development under natural conditions. The map-based cloning results demonstrated that Dapeimi is a novel allelic mutant of the rice GIANT EMBRYO (GE) gene, and the functional mutation site is a single cytosine deletion in the exon1. A total of 285 differentially accumulated metabolites (DAMs) and 677 differentially expressed genes (DEGs) were identified between NIL-D and NIL-X. The analysis of DAMs indicated that plants lacking GE mainly promoted energy metabolism, amino acid metabolism, and lipid metabolism pathways in the rice embryo. Pearson correlation coefficient showed that 300 pairs of gene-metabolites were highly correlated. Among them, OsZS_02G0528500 and OsZS_12G0013700 were considered to be key genes regulating L-Aspartic acid and L-Tryptophan content during rice giant embryo development, which are promising to be good candidate genes to improve rice nutrition. By analyzing rice embryo development through a combination of strategies, this research contributes to a greater understanding of the molecular mechanism of rice embryo development, and provides a theoretical foundation for breeding high-nutrition varieties.